Halloysite infused jute fiber/poly (3-hydroxy-butyrate-co-3-valerate) bionanocomposites: Thermal, mechanical and fire retardant properties. (November 2022) - Hasan, Kamrul SM; Zainuddin, Shaik; Turner, Azizi J; Hosur, Mahesh V; Jeelani, Shaik
Biocomposites have become more mainstream over the past decades for preserving the environment and producing sustainable materials as a potential substitute to synthetic polymer based composites derived from scarce petroleum materials. However, it is essential to investigate their mechanical, thermal and fire retardancy performance to answer the question of their suitability in automobile, biomedical, construction, film packaging, and commercial industries. In this work, we have studied one such promising biocomposites, jute fiber/poly (3-hydroxy-butyrate-co-3-valerate) (PHBV) and investigated their aforementioned properties. At first, 3–15 wt% halloysite nanotubes (HNTs) were dispersed in PHBV/chloroform mixture using an ultrasound process. PHBV/HNTs thin films were then prepared using the solvent casting method. Finally, jute fiber/PHBV-HNTs bionanocomposites were prepared using the compression mold method. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) tests were performed to study the thermal and fire retardancy properties. Uniaxial tensile and flexure tests were also performed to investigate the mechanical properties. In addition, scanning electron microscopy (SEM) was carried out to analyze the fracture surfaces of flexure tested samples. Results of jute/PHBV composites showed a significant increase in thermal and mechanical properties at 5 wt% HNTs loading in comparison to neat composites (without HNTs). In contrast, the composites with 15 wt% loading showed superior fire retardancy. SEM images of flexure tested samples showed enhanced interfacial bonding and less fiber pullout when compared to neat counterparts.